Synthesis and biological evaluation of novel anti-tumour (E)-styrylsulfonyl methylpyridines - Lu, Tiangong (2014)
ON01910.Na (Rigosertib, Estybon®), a styryl benzylsulfone, is a Phase III stage anti-cancer agent. This non-ATP competitive kinase inhibitor has multi-targeted activity, promoting mitotic arrest and apoptosis. Extensive Phase I/II studies with ON01910.Na, conducted in patients with solid tumours and haematological cancers demonstrate excellent efficacy. However, issues remain affecting its development. These include incomplete understanding of anti-tumour mechanisms, low oral bioavailability and unpredictable pharmacokinetics. In an attempt to improve drug-likeness and ADME properties of ON01910.Na analogues, a novel series of (E)-styrylsulfonyl methylpyridine derivatives was designed and synthesised. The SAR of this novel series is discussed. The lead compounds TL-68, TL-77, and AH-123 are highly potent mitotic inhibitors. Their selective cytotoxicity to cancer cells was identified in the screening cascade. Impressively, TL-77 possesses excellent pharmaceutical properties, with improved oral bioavailability when compared to ON01910.Na. The detailed cellular mechanisms of TL-77 were further investigated in comparison with ON01910.Na. TL-77 exhibits potent anti-proliferative activity against a wide range of human tumour cell lines, and demonstrated > 2 fold greater potency in cancer cell lines over normal cells.. Cell cycle analyses reveal that TL-77 evokes profound G2/M cell cycle arrest at ≥ 6 h in cancer cells, followed by the onset of apoptosis. In cell-free conditions, TL-77 as well as ON01910.Na potently inhibits tubulin polymerization. Mitotically arrested cells display multipolar spindles and misalignment of chromosomes, indicating TL-77 interfere mitotic spindle assembly in cancer cells. These effects are accompanied by induction of DNA damage, inhibition of Cdc25c (Ser198) phosphorylation [indicative polo-like kinase 1 (Plk1) inhibition], and downstream inhibition of cyclin B1. However, kinase assays failed to confirm the inhibition of Plk1. Non-significant effects on PI3K/AKT signal transduction are observed after TL-77 treatment. Analysis of apoptotic signalling pathways reveals that TL-77 down-regulates expression of B-cell lymphoma 2 (Bcl-2) family proteins [Bid (BH3 interacting-domain death agonist), Bcl-xl (B-cell lymphoma-extra large) and Mcl-1 (induced myeloid leukaemia cell differentiation protein)] and stimulates caspase activation. These effects are comparable to those elicited by ON01910.Na. Unlike ON01910.Na, however, TL-77 causes preferential toxicity in cancer cells when compared to normal cells and mediates rapid mitotic inhibitory effects. In summary, selective in vitro anti-tumour activity and multi-faceted mechanisms of action of a novel molecule TL-77 have been identified, presenting a strong rationale for further development of (E)-styrylsulfonyl methylpyridine derivatives as therapeutic agents for cancer.